Pelatihan Penelitian Tindakan Kelas (PTK) dan Penulisan Karya Ilmiah Bagi Guru-Guru SD Di Sesela - Nurul Hikmah; Ketut Sarjana; Tabita Wahyu Triutami; Nilza Humaira Salsabila; Eka Kurniawan (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
The class action research and scientific article writing activity was done to increase teachers’ professionalism. This training was carried out for the teachers of SDN 2 Sesela, West Lombok. The program was presented in SDN 2 Sesela in the form of workshop through discussion, question and answer session, and speech. The presentation covered class action research and its urgency for the teachers, teaching models that support free learning curriculum, making innovative instructing tools as teaching media in class. The importance of CAR scientific article writing for teachers and its publication in scientific journals. The high motivation and enthusiasm of the participants was obvious during the program. In addition, the participants’ response was positive with enthusiasm rate at 90 percent. The satisfaction rate of the teachers for this activity corresponds to the positive result of this project. Eventually, the teachers hope that further activities like in class CAR implementation will be held following this program.